Investigating how historical legacies of militarized violence can motivate COVID-19 vaccine hesitancy: Evidence from global dyadic survey. (October 2022) - Kobayashi, Yoshiharu; Howell, Christopher; Heinrich, Tobias; Motta, Matthew
Abstract: Background: In almost all countries, COVID-19 vaccines available for public use are produced outside of that country. Consistent with recent social science research, we hypothesize that legacies of violent conflict from vaccine-producing against vaccine-consuming countries may motivate vaccine hesitancy among people in targeted countries that purchase vaccines produced by the erstwhile aggressor. Methods: Our analyses draw on data from the Correlates of War project and a large, representative survey of 18, 291 adults that asked respondents in 16 countries to self-report their attitudes toward COVID-19 vaccines originating from 12 potential vaccine-producing countries in December 2020 (184 country-pairs, 208, 422 ratings). For the main analysis, we used random-effect linear probability models and turned to Bayesian Model Averaging to probe the robustness of the main findings. Results: We demonstrate that elevated levels of historical violence between vaccine-producing and vaccine-consuming countries are associated with increased negative feelings toward a COVID-19 vaccine produced by the vaccine producer. Conclusion: Global vaccine hesitancy may result, at least in part, from public perceptions of historical conflict between vaccine-producing and vaccine-consuming countries. These results can help public health practitioners better preempt and adjust for cross-national vaccine resistance. Highlights: We study whether legacies of inter-country violence motivate vaccine hesitancy. Dataset covers 12 foreign vaccines and 18, 291 individuals across 16 countries. Violent histories are associated with negative views on specific foreign vaccines. Results are robust across age, education, and gender groups.